Urban Design Guidelines for Climate Change - Takebayashi, Hideki; Yuan, Jihui (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue consists of 13 submitted papers. We acknowledge all authors for their contributions. We recognize that interest in the topics is expanding and are confident that the findings are beneficial to our readers.